PENGGUNAAN JENIS MEDIA DAN PERLAKUAN PUPUK UNTUK PERTUMBUHAN ANGGREK DENDROBIUM - Lianawati, Ida Ayu Meva; Adriani Astiti, Ni Putu; Suriani, Ni Luh (SIMBIOSIS, 2021)
ABSTACT Reseach on dendrobium orchids was planted in the media of wood charcoal and coconut fibers and it is needed with Gandasil B fertilizer wood charcoal and coconut fiber media and is needed with Gandasil B and Multitonik fertilizer. This study aims to determine the effect of media and fertilizer on orchid growth and to determine pests and diseases in Dendrobium orchid plants. This reseach was conducted in May until July 2019 in the Plant Physiology Laboratory Biologi Prodi Studi Biologi Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Udayana. Qualitative and quantitative data are used that combine the Gandasil B fertilizer and fibers and wood charcoal media Fertilizer Gandasil B fertilizer with concetration G 0 (0 g L -1 ), G 2 (20 g L -1 ), G 3 (30 g L -1 ), G 4 (40 g L -1 ), G 5 (50 g L -1 ). Fertilizer Multitonik M 0 (0 g L -1 ), M 1 (1,1 g L -1 ), M 2 (1,2 g L -1 ), M 3 (1,3 g L -1 ), M 4 (1,4 g L -1 ), M 5 (1,5 g L -1 ). Each fertilizer concentration was repeated 6 times.  The results showed the best orchid growth was found in the use of Multitonik fertilizer and the best orchid growth was found in the use of Multitonik number of leavers and root growth were found in the use of coconut fibers media